Moral Thinking and the stages of its Development in humans A Comparative Study of the theories of Lawrence Kohlberg and Carol Gilligan - خرما, إيفا; شريقي , مدى; عباس, ذكريا (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research deals with the concept of development of moral thinking and how the individual's moral awareness is formed by social education that sets values, standards, and moral principles, which affect the moral judgments on attitudes, things and actions at different stages of life. It also deals with some of the factors that affect the development of individual’s moral thinking such as gender, age, socio-cultural environment and cognitive formation. It reviews the levels of development of moral thinking in males and females and their stages, that are based on the theories of Lawrence Kohlberg and Carol Gilligan. Moreover, it highlights the most important points of similarity and difference in the nature of the development of moral thinking in males and females.